Pengaruh Profitabilitas, Struktur Modal, Pengelolaan Kas, dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2023 - Putri Rahayu; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine how factors like profitability, capital structure, cash management, and company size affect the financial performance of manufacturing companies in the food and beverage subsector that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Analysis is essential. The Smart PLS technique and secondary data from the financial statements of seven companies selected through purposive selection are used in the quantitative methodology of this study. Financial performance is evaluated using Tobin's Q and EPS, and the independent factors that are looked at include ROE, DER, quick ratio, current ratio, and total assets. The study's findings indicate that while business size has no discernible effect on financial performance, return on investment (ROE) has a strong positive influence. Nevertheless, capital structure (DER) has a negative impact on financial performance while company size has a positive one; neither effect is statistically significant. Additionally, cash management has a little negative impact on financial success, but business size has a positive and significant influence. However, there is a small but favorable correlation between firm size and financial performance.